A review on the scope and challenges of Saccharum spontaneum waste in the context of lignocellulosic biomass for sustainable bioenergy applications - Srivastava N.; Singh P.; Srivastava M.; Lal B.; Singh R.; Ahmad I.; Gupta V.K. (My University, 2025)
Bioenergy production from lignocellulosic biomass waste is among the most promising options to produce sustainable economic fuel in an eco-friendly way. This review is an attempt to use and explore Saccharum spontaneum grass as a potential lignocellulosic biomass waste to produce bioenergy. Many advantages, like high cellulose and hemicellulose content, renewable nature, huge availability, and non-participation in the food chain, make this biomass a waste of immense interest. Nevertheless, existing challenges and limitations need to be addressed in view of sustainable bioenergy production from this biomass. In this review, an overview of the utilization of waste Saccharum spontaneum grass as a potential feedstock for developing bioenergy has been provided in view of its physicochemical properties, which are fascinating from the perspective of renewable energy production. Furthermore, advanced and lower-cost strategies are being discussed, along with the possible challenges found in pretreatment, bioconversion, and bioenergy production using lignocellulosic biomass. In view of available research studies on the utilization of Saccharum spontaneum grass to produce bioenergy, numerous processes and key strategies have been discussed and evaluated with those of different LCBs for the production of renewable energies. Additionally, existing limitations and future scope, along with possible solutions in the process of producing green energy, have been discussed. © 2024 Elsevier Ltd